Comparative nesting patterns and success of Mynas and Starlings (Aves: Sturnidae) inhabiting Jahangirnagar University campus, Bangladesh (Bangladesh Journal of Zoology, 2021)
Nesting patterns of four species of mynas and starlings, Common Myna (Acridotheres tristis), Jungle Myna (Acridotheres fuscus), the Asian-pied Starling (Gracupica contra) and Chestnut-tailed Mtarling (Sturnia malabarica) were studied in Jahangirnagar University campus from March to September in 2016. Nests were searched systematically throughout the study area and nesting parameters like nest dimensions, nest-site selection, tree species preference, nesting materials, clutch size and nesting success were examined. A total of 101 nests were recorded where 31 nests were of Common Myna, 10 of Jungle Myna, 49 of the Asian-pied Starling and 11 nests were of Chestnut-tailed Starling. Overall, the sturnids preferred nesting on trees (n=84) to anthropogenic structures (n=17). Common myna showed maximum variation in nest-site selection using tree holes (n=12), tree branches (n=10) and building cornices, holes or crevices (n=9) whereas Chestnut-tailed Starling nested only in tree cavities (n=11). Jungle Myna built nests both in tree holes (n=4) and in building holes and crevices (n=6). The Asian-pied Starlings built their domed nests mostly on tree branches (n=47) where 69% nests were peripheral and 31% were central in position. Out of 20 species of trees utilized for nesting purpose, the majority of nests were built on Whites iris Albizia procera (n=18) followed by Neem Azadirachta indica (n=10) and Mahogany Swietenia mahagoni (n=10). The nests were constructed between 2 and 18m (8±3.8m) from the ground level. Among 19 types of nesting materials recorded, twigs, leaves, straws, grasses, feathers, plastics and polythene were frequently used by all four species while the Asian-pied starling used more rubbish materials than other species. Highest nesting success (80%) was recorded in Common Myna whereas the Asian-pied Starling, Chestnut-tailed Starling and Jungle Myna had 77.8%, 75% and 66.7% of nesting success respectively. Adaptions to using different nesting sites in Common Myna and comparatively higher nesting height in the Asian-pied Starling may have facilitated the greater nesting success.Bangladesh J. Zool. 48(2): 321-334, 2020